WHAT DOES A TEACHER ACTUALLY DO IN THE CLASSROOM? ANALYSIS OF RESEARCH ON TEACHING ACTION - Bremm, Daniele; Arruda, Sergio de Mello; Passos, Marinez Meneghello (Seven Editora, 2025)
This article presents a mapping of theses and dissertations prepared by a research group that has been investigating Teaching Action for over ten years, from different perspectives. The data collection was conducted in the repository of the graduate program to which the research group belongs. The research, which adopted a qualitative and exploratory approach, followed the procedures of Discursive Textual Analysis to organize and interpret the collected data. Its objectives were to identify different contexts, investigative approaches, and theoretical foundations used by the researchers, as well as to analyze and seek new understandings regarding the categories of Teaching Action found in the theses and dissertations. The process of analyzing the categories of Teaching Action resulted in nine final categories, which express what the teacher actually does in the classroom: teach about the content; manage the class and time; engage students’ attention; use different technological resources; supervise the completion of activities; socialize on various topics; assign activities; encourage students to complete activities; and evaluate activities developed by students. DOI: https://doi.org/10.56238/sevened2025.038-071